Sex-specific effects of a microsatellite polymorphism on human growth hormone receptor gene expression. (15th July 2019) - Dias, Christel; Elzein, Samar; Sladek, Robert; Goodyer, Cynthia Gates
Abstract: Growth hormone (GH) binds to its specific receptor (GHR) at the surface of target cells activating multiple signaling pathways implicated in growth and metabolism. Dysregulation of GHRs leads to pathophysiological states that most commonly affect stature. We previously showed the association of a polymorphic (n = 15–37) GT microsatellite in the human GHR gene promoter with short stature in a sex-specific manner. In the present study we evaluated the functional relevance of this polymorphism in regulating GHR expression. Using luciferase reporter assays, we found that the GT repeat had a significant cis regulatory effect in response to HIF1α and a potential repressor role following C/EBPβ stimulation. Using a digital PCR application to measure allelic imbalance (AI), we showed a high prevalence of AI (∼76%) at the GHR locus in lymphoblastoid cell lines (LCLs), with a significantly higher degree of imbalance in LCLs derived from males. Examination of expression of GHR as well as other members of the GH-IGF1 axis in the LCLs revealed significant associations of GHR, IGF1 and BCL2 expression with GT genotype in a sex-specific manner. Our results suggest that this GT microsatellite exerts both cis and trans effects in a sex-specific context, revealing a new mechanism by which GHR gene expression is regulated. Highlights: GHR transcriptional activity is regulated by a GT repeat microsatellite polymorphism in a context and sex-specific manner. GHR expression shows a high degree of allelic imbalance in males. Functional studies suggest cis effects of the microsatellite on GHR as well as potential trans effects on IGF1 and BCL2.